2002
DOI: 10.1088/0957-4484/13/2/301
|View full text |Cite
|
Sign up to set email alerts
|

Nano-rubbing of a liquid crystal alignment layer by an atomic force microscope: a detailed characterization

Abstract: Locally rubbing the surface of a polymer using the stylus of an atomic force microscope (AFM nano-rubbing) has recently found extensive applications in prototyping novel micro-and nano-structured liquid crystal (LC) electro-optic devices. We report here on the detailed characteristics of the AFM nano-rubbed polyimide in terms of the friction force and the LC alignment capability. A unidirectionally rubbed polyimide by the contact mode AFM showed anisotropic friction, along and against the rubbing direction, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 23 publications
0
51
0
1
Order By: Relevance
“…The maximum anchoring energy of patterned ITO is 3.96Â10 À4 N m À1 , a value that is comparable to those of conventional rubbed PIs (10 À4 -10 À5 N m À1 ) and surfaces rubbed by using AFM (10 À6 N m À1 ). 26 The minimum anchoring energy is 7.75Â10 À8 N m À1 , which is 5100 times lower than the maximum value. Maximum and minimum anchoring energies were calculated using the line with l ca 200 nm and A ca 155 nm (Supplementary Figure S5) and the line with l ca/ 1000 nm and A ca 25 nm (Supplementary Figure S7), respectively.…”
Section: Discussionmentioning
confidence: 85%
“…The maximum anchoring energy of patterned ITO is 3.96Â10 À4 N m À1 , a value that is comparable to those of conventional rubbed PIs (10 À4 -10 À5 N m À1 ) and surfaces rubbed by using AFM (10 À6 N m À1 ). 26 The minimum anchoring energy is 7.75Â10 À8 N m À1 , which is 5100 times lower than the maximum value. Maximum and minimum anchoring energies were calculated using the line with l ca 200 nm and A ca 155 nm (Supplementary Figure S5) and the line with l ca/ 1000 nm and A ca 25 nm (Supplementary Figure S7), respectively.…”
Section: Discussionmentioning
confidence: 85%
“…2). The much larger-scale morphological relaxation of the surface scratches seen by Kim et al 12 with low-temperature annealing shows that significant relaxation occurs at the surface with heating. The relaxation seen here, though at a much smaller scale, may be of a similar origin.…”
Section: Rubbing Before Imidizationmentioning
confidence: 87%
“…10 Higher temperatures during rubbing have also resulted in increased orientation of the polyimide films. 11 Kim et al 12 have shown morphological relaxation in scratches in the polyimide surface due to low-temperature annealing, after which the scratched areas retained their ability to align liquid crystals. Kikuchi et al 1 have found that BPDA-PDA, the polyimide used in this study, will even align smectic liquid crystals when imidized or cured at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…As observed in Figure 15 from height profiles the nanochannels created in PI4 film surface are of 45 nm depth and 50 nm wide, while for the PI5 film they have smaller dimensions, namely 10 nm depth and 20 nm wide. The surface ordering induced by DPL in case of Epiclon-derived PIs is more pronounced comparatively with other commercial PIs [71], making them more suitable for LCDs applications. The differences regarding the size of the nanochannels for PI4 and PI5 can be correlated with their surface mechanical properties.…”
Section: Importance Of Mechanical Surface Properties On Pi Morphologymentioning
confidence: 99%